JAPAN’S ECONOMIC SITUATION OVER THE LAST 10 YEARS - Ulug‘murodov F.F; Jamilov F.O (TADQIQOTLAR, 2026)
Abstract.  This  article  is  devoted  to  analyzing  the  development  of  Japan’s economy  in  recent  years  under  conditions  of  global  economic  changes.  The  study assesses post-pandemic recovery processes as well as the main directions of economic and  fiscal  policy.  The  analysis  is  based  on  statistical  data  and  macroeconomic indicators. The results show that Japan’s economy has prospects for sustainable growth up to 2030, with significant opportunities particularly in the  fields of technological development and green energy. The findings of the study are of practical importance for shaping economic policy and directing investments toward priority areas.